The linker-loop region of Escherichia coli chaperone Hsp31 functions as a gate that modulates high-affinity substrate binding at elevated temperatures - Sastry, M. S. R. (National Academy of Sciences, 2004)
Precise control of substrate binding and release is essential for molecular chaperones to exert their protective function in times of stress. The mechanisms used are diverse and have been difficult to unravel. Escherichia coli heat-shock protein 31 (Hsp31) is a recent addition to the known complement of eubacterial chaperones. Crystallographic studies have revealed the presence of a hydrophobic bowl at the Hsp31 dimer interface and shown that the linker region connecting the two structural domains within each subunit is disordered. Together with a neighboring flexible loop, the linker caps a hydrophobic area adjacent to the bowl. Using a collection of Hsp31 mutants, we show that although both bowl and linker-loop-shielded residues participate in substrate binding, the latter are critical for protein capture at high temperature. Linker immobilization via an artificial disulfide bridge abolishes chaperone activity at elevated temperatures by precluding exposure of the underlying hydrophobic domain. We conclude that Hsp31 uses its linker-loop region as a thermally activated gate to control nonnative protein annealing to a high-affinity substrate-binding site. This simple yet efficient strategy to capture partially folded proteins under heat-shock conditions may be shared by other folding modulators.